Method of Moments for the Two-Dimensional Analysis of Array-Fed Metasurface Antennas - DESSY, Jonathan; BODEHOU, Modeste; CRAEYE, Christophe (My University, 2024)
This paper presents a Method of Moment (MoM) formulation for the two-dimensional analysis of array-fed metasurface (MTS) antennas. In the considered problem, the MTS is only modulated along one direction and translationally invariant along the other one. The MoM is first formulated for the case of a MTS of finite length fed with an array of active elements, with no particular constraint on the feed spacing, nor on the weight associated with each element. Then, the methodology is particularized to the case of a periodic MTS fed with an infinite array of active elements of same amplitude, with constant feed spacing and linear phase shift between elements. In both cases, the implementation is closely analysed and simulation results are shown to cross-validate both approaches. It can be concluded that the implemented methodologies can provide very fast and accurate results.
Keywords: Metasurface (MTS); array; Method of Moments (MoM); periodic.